2020
DOI: 10.5564/pmas.v60i3.1424
|View full text |Cite
|
Sign up to set email alerts
|

A study on structure and functions of organs involved in the formation of Mongolian Khuumii sound

Abstract: Khuumii (throat or overtone singing) is a unique form of art derived from the nomadic population of Central Asia, which is a type of singing in which the singer manipulates the resonances (or formants) created as air travels from the lungs, past the vocal folds, and out of the lips to produce a melody. A total of 60 participants, aged 18-60 years (54 men and 6 women), were selected by non-random sampling method using cross-sectional study. X-ray, endoscopy, and sound research method were used in the study, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The application of electrical impedance tomography in brain imaging, especially in stroke detection [ 17 , 18 ], attracts a lot of interest due to its relatively low cost, absence of side effects, and the possibility of developing wearable solutions [ 19 ]. Poor blood flow to the brain tissues during a stroke may be caused by a lack of blood flow (ischemic stroke) or bleeding (hemorrhagic stroke) [ 20 , 21 , 22 ]. It has been shown that the conductivity of tissues in stroke-affected areas is significantly different from that of healthy tissues and differs in both stroke types [ 18 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of electrical impedance tomography in brain imaging, especially in stroke detection [ 17 , 18 ], attracts a lot of interest due to its relatively low cost, absence of side effects, and the possibility of developing wearable solutions [ 19 ]. Poor blood flow to the brain tissues during a stroke may be caused by a lack of blood flow (ischemic stroke) or bleeding (hemorrhagic stroke) [ 20 , 21 , 22 ]. It has been shown that the conductivity of tissues in stroke-affected areas is significantly different from that of healthy tissues and differs in both stroke types [ 18 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%